PERBANDINGAN HAMBATAN FINANSIAL PADA SEBELUM DAN SETELAH JAMINAN KESEHATAN DI INDONESIA - Putri Listiani; Julita Hendrartini; Dibyo Pramono (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2022)
Background: Healthcare spending in Indonesia is still dominated by out-of-pocket (OOP) system (45.1% in 2014). The high number of OOP in Indonesia is feared to cause financial burden to society and result in the failure of the financial protection function of a health system, whereby Indonesia is in a scheme to achieve Universal Health Coverage through the Universal Health Coverage program. Objective: This study aimed to compare the financial burden due to OOP on before and after JKN and its determinants. Methods: This was a quantitative study that examines secondary data, including Social Economic National Survey (Susenas) data in 2013 and 2015 with cross sectional design. The unit of analysis in this study was households. Analysis conducted in this research was univariable, bivariable, and multivariable analysis. Multivariable test using Logistic Regression Test was conducted to find out the relationship between the financial burden due to OOP with its determinants. Results: There was a decrease in the proportion of households experiencing catastrophic health care expenditure was 0,59% in 2015. Households on before implementation of JKN period tend to face catastrophic health expenditure than households on after implementation of JKN period (OR= 2,29). Determinants affecting catastrophic health expenditure in Indonesia were the number of household member, educational status of the head of household, the presence of toddler, the presence of elderly in the household, the location of the household residence, the economic status of the household, the ownership of the health insurance, and the utilization of health services. Conclusion: Utilization of inpatient health care services was the most contributing factor to catastrophic health expenditure. House- holds that use inpatient care had a catastrophic health care spend- ing risk of 26,78 times greater than non-accessed households